2020
DOI: 10.3390/ijms21020686
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and Ammonium Affect the Overall Maize Response to Nitrogen Availability by Triggering Specific and Common Transcriptional Signatures in Roots

Abstract: Nitrogen (N) is an essential macronutrient for crops. Plants have developed several responses to N fluctuations, thus optimizing the root architecture in response to N availability. Nitrate and ammonium are the main inorganic N forms taken up by plants, and act as both nutrients and signals, affecting gene expression and plant development. In this study, RNA-sequencing was applied to gain comprehensive information on the pathways underlying the response of maize root, pre-treated in an N-deprived solution, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 94 publications
3
36
0
Order By: Relevance
“…The ERF-LEP ( c296735 ) that was upregulated in T3 has been reported to be involved in leaf petiole development [ 35 ], vascular cell number [ 36 ], and gibberellin-induced germination [ 37 ]. WRKY12’s ( c284230 ) exclusive regulation between ammonium fed masson pine roots is in accordance with a recent report in maize where authors reported similar exclusive expression of WRKY TFs [ 38 ]. Some studies have reported the expression of WRKYs, MADS, and EREBPs in response to N deficiency [ 39 ], but the ammonium regulated functional characterization has not been reported yet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The ERF-LEP ( c296735 ) that was upregulated in T3 has been reported to be involved in leaf petiole development [ 35 ], vascular cell number [ 36 ], and gibberellin-induced germination [ 37 ]. WRKY12’s ( c284230 ) exclusive regulation between ammonium fed masson pine roots is in accordance with a recent report in maize where authors reported similar exclusive expression of WRKY TFs [ 38 ]. Some studies have reported the expression of WRKYs, MADS, and EREBPs in response to N deficiency [ 39 ], but the ammonium regulated functional characterization has not been reported yet.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, it could be stated that masson pine seedlings, when grown solely in NH 4 + , had the ability to tolerate increased NH 4 + supplies by increasing the expression of AS. Furthermore, it is known that N can be redirected from glutamine to asparagine when excess NH 4 + is available [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aminoacidic analysis in triacontanol based biostimulant was performed by HPLC-MS/MS as we previously described [ 25 ]. Briefly, samples were extracted in an ultrasound bath with a solution of diluted HCl (0.5 M) for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Plants have developed an antioxidant machinery that includes the activity of ROS detoxifying enzymes [e.g., SOD, APX, CAT, and Prx], as well as antioxidant molecules such as ascorbic acid (ASA) and glutathione (GSH) that are present in almost all subcellular compartments (Cassia et al 2018). Nitrate starvation repress genes related to the cytoskeleton and ROS detoxi cation (Ravazzolo et al 2020). In our experiment, compared with the control group, SOD, CAT activities decreased after 2 days of N de ciency (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A large genetic variation existed in DEGs related to amino acid, carbon, and nitrogen metabolism. The identi cation of key genes underlying the response to N starvation may enable novel approaches to increase NUE and to improve plant resilience to nutritional stresses(Ravazzolo et al 2020). In tomato, 97 genes are differentially expressed when nitrate is resupplied to nitrate-starved tomato plants within1-96 h…”
mentioning
confidence: 99%